Unraveling the epidemiological relationship between ticks and rickettsial infection in Africa - Onyiche, ThankGod E.; Labruna, Marcelo B.; Saito, Tais B. (Frontiers in Tropical Diseases, 2022)
Tick-borne rickettsioses are emerging and re-emerging diseases of public health concern caused by over 30 species of Rickettsia. Ticks are obligate hematophagous arthropods with over 700 species of Ixodid ticks known worldwide. The escalating geographical dispersal of tick vectors and concomitant increase in the incidences of tick-borne diseases have fueled interest in the ecology of tick-borne pathogens. This review focuses on aspects of the Rickettsia pathogen, including biology, taxonomy, phylogeny, genetic diversity, epidemiology of the disease, and the role of vertebrate host in the perpetuation of rickettsioses in Africa. Our review also highlights some of the species of Rickettsia that are responsible for disease, the role of tick vectors (both hard and soft ticks) and the species of Rickettsia associated with diverse tick species across the continent. Additionally, this article emphasizes the evolutionary perspective of rickettsiae perpetuation and the possible role of amplifying vertebrate host and other small mammals, domestic animals and wildlife in the epidemiology of Rickettsia species. We also specifically, discussed the role of avian population in the epidemiology of SFG rickettsiae. Furthermore, we highlighted tick-borne rickettsioses among travelers due to African tick-bite fever (ATBF) and the challenges to surveillance of rickettsial infection, and research on rickettsiology in Africa. Our review canvasses the need for more rickettsiologists of African origin based within the continent to further research towards understanding the biology, characterization, and species distribution, including the competent tick vectors involved in their transmission of rickettsiae across the continent in collaboration with established researchers in western countries. We further highlighted the need for proper funding to encourage research despite competing demands for resources across the various sectors. We finalize by discussing the similarities between rickettsial diseases around the world and which steps need to be taken to help foster our understanding on the eco-epidemiology of rickettsioses by bridging the gap between the growing epidemiological data and the molecular characterization of Rickettsia species.